2012
DOI: 10.12816/0005998
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Irrigants in the Endodontic Therapy

Abstract: Abstract:This paper highlights the importance of root canal disinfection. It discusses the different endodontic irrigants available and comments on how these can be used most effectively. Eliminating bacteria from the root canal system is an essential stage in endodontic therapy. An objective of endodontic treatment is removal of diseased tissue, elimination of bacteria from the canal system and prevention of recontamination.(1) Disinfection of the root canal system, as part of endodontic therapy, by preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2107
2107

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 16 publications
(36 reference statements)
0
33
0
1
Order By: Relevance
“…Initial etiologic factor in formation of pulp waste and priapical bacteria were studied (Kandaswamy and Venkateshbabu 2010;Guerreiro-Tanomaru et al, 2011;Martin 1991;Mohammadi andAbbott 2009, Portenier et al, 2002). Micro-organisms may be existed in root canal, dentinal tubules, secondary canals and apical strait (Kandaswamy and Venkateshbabu 2010;Baumgartner et al, 2007;Iqbal 2012). In some dentinal teeth, even DEJ was infected (Zehnder et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial etiologic factor in formation of pulp waste and priapical bacteria were studied (Kandaswamy and Venkateshbabu 2010;Guerreiro-Tanomaru et al, 2011;Martin 1991;Mohammadi andAbbott 2009, Portenier et al, 2002). Micro-organisms may be existed in root canal, dentinal tubules, secondary canals and apical strait (Kandaswamy and Venkateshbabu 2010;Baumgartner et al, 2007;Iqbal 2012). In some dentinal teeth, even DEJ was infected (Zehnder et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The best result is obtained from using a good detergent with anti-bacterial activity when it contacts long enough with batteries of root canal system. This means that, for fulfi lling preparation stage before obtuaration, detergent needs to be reached a suffi cient volume during the treatment (Iqbal 2012). It seems that using local medicine is more effective and better that all applicable antibiotic plans (Martin 1991).…”
Section: Bioscience Biotechnology Research Communications Evaluation mentioning
confidence: 99%
“…[8] Calcium hydroxide's anti microbial action is influenced by the speed of its dissociation into calcium ions and hydroxyl ions and by inactivating enzymes of the cytoplasmic membrane of microorganisms, thus causing toxic effects on the bacterial cells; another mechanism of action of this medication is its ability to absorb carbon dioxide, thus leading to the death of CO 2 - dependent bacteria. Chlorhexine may also present residual antimicrobial activity on the dentine surface after prolonged contact within root canal and also improve antimicrobial efficacy against calcium hydroxide resistant microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Rossi-Fedele., et al [46] showed Sterilox not being as effective as NaOCl and again a small study of 15 roots were used in carrying out the study. PAD was mentioned by Iqbal [48] which is an irrigation method involving a solution which can bind to bacteria and then treatment with a laser to irradiate bacteria. It offers advantages of low toxicity however the authors suggested there is no robust evidence to supportthe use of this system.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%